The SCN1A Mutation Database: Updating Information and Analysis of the Relationships among Genotype, Functional Alteration, and Phenotype. Issue 6 (13th April 2015) - Meng, Heng; Xu, Hai‐Qing; Yu, Lu; Lin, Guo‐Wang; He, Na; Su, Tao; Shi, Yi‐Wu; Li, Bin; Wang, Jie; Liu, Xiao‐Rong; Tang, Bin; Long, Yue‐Sheng; et al.
<x xml:space="preserve">Abstract</x> We systematically reviewed SCN1A mutations and established a database with sections detailing functional alteration (funotype) and inheritance. Further analyses indicated a close genotype‐funotype‐phenotype relationship. Mutations located in different sodium channel regions were associated with distinct funotype and subsequently different phenotype severity, suggesting that funotype is critical in evaluating pathogenicity. A negative correlation was found between phenotype severity and familial incidence, incomplete penetrance was associated with missense and splice‐site mutations, but not truncations or genomic rearrangements, suggesting clinical genetic counseling applications.